Socioeconomic context of the production and utilization of alcoholic herbal remedy in Ibadan, Nigeria (2013)
Pàrâgà - a Yoruba herbal remedy containing local herbs and gin is claimed to be effective in the treatment of piles, backaches, and male erectile problems. Believed to be more effective than some biomedical drugs for these ailments, pàrâgà raises questions concerning the use of alcohol in the herbal drug, characteristics of its producers and the users, and its health implications in Ibadan. Through ethnography, the influence of certain socioeconomic factors on pàrâgà production and utilization in Ibadan is examined. Nigeria's underdeveloped health care system, poor health education, and high cost of biomedical drugs compel the users of pàrâgà to use it as an alternative health mea sure. Producers are mostly women with low income, while the users are mainly low-income men. Users always use and abuse it as intoxicant. Pàrâgà, a herbal remedy containing alcohol needs to have its production and consumption regulated. It is also necessary to engage Ibadan's public in culturally sensitive health education on the risks associated with alcoholic herbal remedies.